Parent, child, and environmental predictors of vegetable consumption in Italian, Polish, and British preschoolers - Masento, Natalie A.; Dulay, Katrina May; Harvey, Kate; Bulgarelli, Daniela; Caputi, Marcella; Cerrato, Giuseppina; Molina, Paola; Wojtkowska, Katarzyna; Pruszczak, Dominika; Barlińska, Julia; Messer, David; Houston-Price, Carmel (Frontiers in Nutrition, 2022)
This paper compared the vegetable intake of preschool children from three European countries (Italy, Poland & UK) and explored the parent, child and environmental factors that predicted intake in each country. 408 parents of preschoolers (Italy: N = 61; Poland: N = 124; UK: N = 225; child mean age = 32.2 months, SD = 9.47) completed an online survey comprising a set of standardized questionnaires. In all three countries, questionnaires included measures of children’s vegetable intake (VegFFQ), child eating behaviour (CEBQ-FF), parents’ mealtime goals (FMG), and socio-demographic questions about the family background and environment. In the UK and Italy, additional questionnaires assessed child temperament (EAS-T) and parents’ feeding practices (CFPQ). Results showed that the number of child-sized portions of vegetables consumed per day varied significantly across countries; Polish children consumed the most (~3 portions) and Italian children the least (~1.5 portions). Between-country differences were seen in parents’ goals for family mealtimes; compared to Italian parents, Polish and UK parents were more motivated to minimize mealtime stress, increase family involvement in meal preparation and for family members to share the same foods. UK and Italian parents also adopted different feeding practices; parents in UK reported more use of healthy modeling behaviours and more use of foods to support their child’s emotion regulation. In terms of child factors, Italian children were reported to be more emotional and more sociable than UK children. Analyses of the relationships between the parent, child and environmental factors and children’s vegetable intake revealed both similarities and differences between countries. Negative predictors of vegetable intake included child food fussiness in UK and Poland, child temperament (especially, shyness) in Italy, and the use of food as a reward and child emotionality in UK. Positive predictors included the parental mealtime goal of ‘family involvement’ in UK. These results highlight differences in the extent to which European preschoolers achieve recommended levels of vegetable intake and in the factors that influence whether they do. The results suggest a need to develop healthy eating interventions that are adapted to meet the specific needs of the countries in which they are implemented.